2021
DOI: 10.1212/cpj.0000000000000965
|View full text |Cite
|
Sign up to set email alerts
|

Elective Hospitalizations for Intractable Headache

Abstract: ObjectiveTo review our inpatient experience treating a variety of headache disorders with heterogeneous therapies and to determine outcomes and predictors of response.MethodsWe conducted an IRB-approved retrospective chart review of elective inpatient headache admissions from the Montefiore Headache Center from 2014-2018. We examined factors associated with response and outcomes at discharge and post-hospitalization follow-up in an intractable population. Patients received different classes of intravenous medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…It is also worth noting that recent reviews of inpatient headache treatment experiences do not report promethazine use in any formulation, suggesting that it is already not used in standard practice at some institutions. 9 , 10 Alternative antiemetics and administration routes can be considered, including intramuscular (IM) promethazine, IV or IM prochlorperazine, and IV or IM ondansetron, as well as oral formulations if tolerated. If IV promethazine must be used concurrently with DHE then it is recommended to administer it through a separate IV line.…”
Section: Discussionmentioning
confidence: 99%
“…It is also worth noting that recent reviews of inpatient headache treatment experiences do not report promethazine use in any formulation, suggesting that it is already not used in standard practice at some institutions. 9 , 10 Alternative antiemetics and administration routes can be considered, including intramuscular (IM) promethazine, IV or IM prochlorperazine, and IV or IM ondansetron, as well as oral formulations if tolerated. If IV promethazine must be used concurrently with DHE then it is recommended to administer it through a separate IV line.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have advocated for early IV and oral corticosteroids to treat new daily persistent headache, particularly if there is an infectious trigger 52 . An elective hospitalization for repetitive IV dihydroergotamine with other parenteral medications including lidocaine or ketamine may help some patients with new daily persistent headache 53-56 . An anecdotal report of just four patients treated with doxycycline 57 led to hundreds if not thousands of patients being treated with this antibiotic course as it has been postulated to have anti-inflammatory properties, but given the lack of evidence for any headache disorder and the potential for serious adverse effects, this treatment is not recommended.…”
Section: Managementmentioning
confidence: 99%
“…However, a 2020 study showed that greater occipital nerve blocks were not as efficacious as IV metoclopramide as first-line therapy for migraine attacks in the emergency department 45 . Peripheral nerve blocks may be used in addition to repetitive IV medications for patients electively admitted for intractable migraine 46 …”
Section: Peripheral Nerve Blocksmentioning
confidence: 99%
“…45 Peripheral nerve blocks may be used in addition to repetitive IV medications for patients electively admitted for intractable migraine. 46 For cluster headache, two randomized clinical trials demonstrated greater occipital nerve injections of steroid (either betamethasone or cortivazol [not available in the United States]) ipsilateral to the side of the pain as superior to placebo for short-term prevention, either as a single injection or in repeated injections over a few days. 4,5 This intervention provides an additional option to oral steroids for short-term cluster headache prevention.…”
Section: Commentmentioning
confidence: 99%